THE ANALYSIS OF INCOME INEQUALITY IN INDONESIA DURING COVID-19: A REVIEW OF POLICY RESPONSES - Kiky Indah Sari; Ciplis Gema Qori'ah; M. Abd. Nasir; Adhitya Wardhono; Adiet Try Waluyo (Jurnal REP (Riset Ekonomi Pembangunan), 2023)
The Covid-19 pandemic has affected the economy from both the supply and demand sides. Policies are designed coherently and quickly, especially monetary and fiscal stimulus. However, the network effect of Covid-19 and global uncertainty can be a challenge in implementing a policy. The motivation behind this study is to determine the response of fiscal and monetary policies to income inequality in Indonesia pra-pandemic and during the period of Covid-19 pandemic. The dataset used in this study is panel data which consists of 25 provinces in Indonesia and period from 2017 – 2021. The estimation method used to identify the response of monetary and fiscal policy to income inequality in Indonesia is Dynamic GMM. This study found that only fiscal policies were effective in reducing inequality in Indonesia before the Covid-19 pandemic. Then during the Covid-19 pandemic period, this study found that monetary and fiscal policies were effective in reducing inequality in Indonesia. This condition shows that the stimulus issued by the government is effective in the sense that it can be a cushion to prevent widening inequality during the Covid-19 period. Overall, this study implies that policy synchronization between fiscal and monetary is needed to minimize the economic impact during the Covid-19 pandemic